1996
DOI: 10.1029/96gl01626
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic discrimination of pyrrhotite‐ and greigite‐bearing sediment samples

Abstract: By using bulk samples, rock magnetic measurements were performed to discriminate between pyrrhotite‐ and greigite‐bearing shallow marine sediments that are now uplifted above sea level in southwestern Taiwan. Thermal demagnetization of a composite isothermal remanent magnetization (IRM) was found to be effective in differentiating between the two types of sediments. To check the thermal instability and estimate the true unblocking temperature (TB) spectra of sediments containing these minerals, saturation IRMs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 19 publications
2
62
0
Order By: Relevance
“…Despite values of magnetic concentration parameters are higher in A9 than A8 and E601, a slight decrease instead of an increase appear s in core A9 during this period. As many previous research suggested (Berner et al 1979;Cutter and Velinsky 1988; Torii et al 1996;Sternbeck and Sohlenius 1997), magnetite can transform to iron sulfides within the reductive environment of coastal waters. Compared to A8 and E601, contribution of component 2 (greigite) reached a relatively high level in sediments of core A9 (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Despite values of magnetic concentration parameters are higher in A9 than A8 and E601, a slight decrease instead of an increase appear s in core A9 during this period. As many previous research suggested (Berner et al 1979;Cutter and Velinsky 1988; Torii et al 1996;Sternbeck and Sohlenius 1997), magnetite can transform to iron sulfides within the reductive environment of coastal waters. Compared to A8 and E601, contribution of component 2 (greigite) reached a relatively high level in sediments of core A9 (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Although high-temperature methods such as Curie point measurement are well established, such measurements can encounter difficulties when samples are heated above -300°C because of the artificial authigenic production of magnetic minerals (Holm and Verosub, 1988;Torii, 1995). Thermochemical changes of the magnetic minerals also hinders straightforward interpretation of the results (van Velzen and Zijderveld, 1992;Torii et al, 1996). Unlike the high-temperature methods, low-temperature experiments are free from thermochemical change and/or artificial production of minerals (Mauritsch and Turner, 1975).…”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…We calculated the IRM difference for each temperature step (AIRM/AT) to better show stepwise changes in IRM intensity occurring during the sample warming (Torii et al, 1996). Figure 3 shows typical examples of thermal demagnetization curves of IRM.…”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…It is difficult in general to indicate explicitly the presence or absence of greigite using rock magnetic methods. Greigite does not show any phase transition below room temperature (Torii et al, 1996). Snowball (1997a, b) and Hu et al (1998) reported that single-domain greigite acquires a significant gyroremanent magnetization (GRM) and rotational remanent magnetization (RRM), and that AF demagnetization of greigite-bearing natural samples based on the static three-axis method showed acquisition of GRM at higher demagnetization fields.…”
Section: Discussionmentioning
confidence: 99%